P11.47 Generation, characterisation and drug screening of patient-derivedIDH1-mutated glioma cell lines. (6th September 2019) - Verheul, C; Kers, T V; Van Der Ploeg, A; Van Der Kaaij, M; Aghababazadeh, M; De Wit, M; Hoogstrate, Y; Struys, E; Dirven, C M F; Leenstra, S; French, P J; Lamfers, M L M
Abstract: BACKGROUND: Despite considerable scientific efforts, endogenous in vitro isocitrate dehydrogenase ( IDH )-mutated glioma models remain scarce. Availability of these models is key to understanding underlying molecular mechanisms and vital for the development of new therapeutic interventions. We established and characterized a set of seven cell lines derived from IDH1 -mutated gliomas and utilized them to investigate IDH -mutant glioma drug-response in vitro. MATERIAL AND METHODS: Fresh tumor material was collected directly from the operating room, mechanically and enzymatically dissociated and cultured under serum-free culture conditions. IDH mutation status was verified at several passages with Sanger sequencing, as well as with whole exome sequencing. D-2-hydroxyglutarate (D2-HG) levels were determined with mass-spectrometry. Genome-wide methylation profiling was performed using the Infinium MethylationEpic BeadChip array. Cell viability was measured using the ATP-based CellTiter-Glo assay. Cell proliferation was determined through cell counting. Drug screens were performed with an FDA-approved anti-cancer drug set from the NIH as well as two IDH-mutant specific inhibitors. RESULTS: Over the last decade our lab processed over 800 glioma samples from all WHO grades and IDH mutational status. Optimisation of culture conditions led to the establishment of seven IDH1 -mutant glioma cell lines. The IDH1 -mutation was present during all tested passages in these cell lines. Whole exome sequencing showed a high concordance between tumor and cell lines with regard to driver gene mutations. Similarly, copy-number changes based on genome-wide methylation data also show a close resemblance between the parental tumor and resulting cell lines. The Heidelberg methylation profiler classified each cell line and its parental tumor as IDH mutant glioma. When exposed to an IDH1-mutant specific inhibitor, all cell lines showed a concentration-dependent decrease of D2-HG levels. The inhibitors showed little to no effect on viability up to 10uM during 8 days, however, long term treatment up to 4 weeks revealed a decrease in cell doubling time in 2 of 6 cultures. Drug screen results either alone or in combination with an IDH1-mutant specific inhibitor identified several interesting candidates that are currently followed up in additional experiments. CONCLUSION: We established a unique set of patient-derived IDH1 -mutant glioma cell lines that closely resemble their respective tumors and can be used to identify new therapeutic strategies.